2014
DOI: 10.1007/s00345-014-1404-4
|View full text |Cite
|
Sign up to set email alerts
|

Initial experiences with the Hemopatch® as a hemostatic agent in zero-ischemia partial nephrectomy

Abstract: Although this study is limited to a small set of initial experiences with Hemopatch(®) in LPN, it proves the feasibility and reliability of this new hemostat. Following further evaluation in prospective randomized comparative studies, Hemopatch(®) might represent a promising tool in NSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 14 publications
2
23
0
1
Order By: Relevance
“…The patch needs no prior preparation and is stored at room temperature [1], allowing rapid availability during surgery. The current case report confirms the patch's utility during surgery, standing alongside critical appraisals of [10,12,13], a shorter mean surgery time [11], and no postoperative complications due to bleeding [15]. Overall, the performance of the collagenbased hemostatic patch for closure of dural defects in cranial surgery was highly satisfactory.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The patch needs no prior preparation and is stored at room temperature [1], allowing rapid availability during surgery. The current case report confirms the patch's utility during surgery, standing alongside critical appraisals of [10,12,13], a shorter mean surgery time [11], and no postoperative complications due to bleeding [15]. Overall, the performance of the collagenbased hemostatic patch for closure of dural defects in cranial surgery was highly satisfactory.…”
Section: Discussionsupporting
confidence: 75%
“…A polyethylene glycol-coated, collagen-based, sealing hemostatic patch (Hemopatch Ò , Baxter Healthcare Ltd.) has been designed to stop bleeding during surgical procedures and to simultaneously induce hemostasis [1,2]. This collagen-based hemostatic patch was safe and performed well against other sealing hemostats when tested in vivo using various surgical models [3][4][5][6][7][8][9], and in a range of surgeries in patients [10][11][12][13][14][15][16][17]. This case report is the first to describe the use of the collagen-based hemostatic patch for repair of vascular injury in a neurosurgical case involving the removal of meningioma in the foramen magnum.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are no data from large clinical studies, but several case reports describe the use of PCC to treat bleeding in patients [28][29][30][31]. Interestingly, Erdas et al demonstrated in a randomized controlled pilot trial that FTC is not superior to standard hemostasis (ligation and use of a harmonic scalpel) in preventing postoperative bleeding risk in patients on antithrombotic therapy with vitamin K antagonists or ASA undergoing thyroid surgery [32].…”
Section: Discussionmentioning
confidence: 99%
“…FloSeal®, pıhtılaşma kaskatının son safhasını taklit eder. Sıfır iskemi tekniği ile yapılan laparoskopik parsiyel nefrektomide yeni bir hemostatik ajan olan Hemopatch®(polyethylene glycol-coated collagen patch, Baxter) kullanılmış ve çalışmalar küçük gruplarla sınırlı olsa da ilk izlenimlerde başarılı sonuçlar elde edilmiş [29].…”
Section: Kitle Eksizyonuunclassified